Initial experience with extracorporeal shock wave therapy in six dogs – part I - Laverty, P. H.; McClure, S. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Extracorporeal shock wave therapy (ESWT) may be an effective treatment modality for delayed or chronic non-union fractures. ESWT is a non-invasive technique that avoids the potential morbidity and mortality associated with traditional surgical procedures, and its use does not preclude subsequent surgical treatment. This case series demonstrates the feasibility, versatility and safety of treating dogs with ESWT.
Keywords: Extracorporal shock wave therapy; orthopaedics; canine